KEWAJIBAN NAFKAH SUAMI NARAPIDANA DALAM KELUARGAPERSPEKTIF WAHBAH AZ ZUHAILI - Khotim, Ahmad; Ansori, Ahmad Insya'; Bahauddin, Ahmad (Usroh, 2025)
The purpose of this research is the obligation of maintenance that should be fulfilled by a husband who is currently serving a sentence. Maintenance is a responsibility that a husband must fulfilll toward his wife in financial form, as the term maintenance is related to material aspects. Meanwhile, non-material responsibilities, such as meeting the wife's sexual needs, are not included in the definition of maintenance, even if the husband does them for his wife. This research applies a qualitative method with a normative theological approach. The use of the qualitative method aims to provide a deeper insight into the issue being studied. The data analysis process uses an inductive approach, which involves developing general conclusions from specific ones. The research results show that the husband's obligation to provide maintenance while imprisoned remains in effect. If the husband serving the sentence is unable to provide for his wife, then that obligation will be suspended and must be fulfilled after the husband completes his sentence. Additionally, Wahbah Az-Zuhaili also emphasized that a wife has the right to file for divorce (khulu') against her husband after the husband has served a minimum of one year in prison due to his inability to fulfilll his financial responsibilities. The urgency of this research is to explain the obligation of spousal support for incarcerated husbands, considering the limitations of the husband's ability and the protection of the wife's rights from the perspective of Wahbah Az-Zuhaili, which is based on justice and the maqāṣid al-syarī‘ah.